Disease Surveillance during the Reintroduction of the Iberian Lynx (Lynx pardinus) in Southwestern Spain - Nájera, Fernando (Animals (Basel), 2021)
SIMPLE SUMMARY: The restoration of Iberian lynx (Lynx pardinus) populations in Extremadura (Southwestern Spain) have been carried out since 2014. To evaluate the effect that infectious diseases may have on their reintroduction, we performed a molecular and sero-epidemiological survey in reintroduced and wild-born lynxes and sympatric carnivores. From 2015 to 2019, 69 Iberian lynxes were screened against 10 viral, bacterial and piroplasmid agents. In parallel, 195 sympatric carnivores were tested against current or past infections to six common canine/feline viruses. In the Iberian lynx, low contact rates of active infection were obtained for feline leukemia provirus (FeLV: 1.5%; 1/67), feline parvovirus (FPV: 1.5%; 1/67) and Cytauxzoon sp. (6.7%; 1/15). We confirmed the emergence of Aujeszky’s disease (suid herpesvirus-1) in this population (SuHV-1: 11.8%; 2/17). We detected the circulation of FeLV, parvovirus, canine distemper virus (CDV), feline calicivirus (FCV) and feline immunodeficiency virus within the sympatric carnivore community and FCV, FPV, CDV and feline coronavirus in lynxes. Due to the low contact rate of infectious agents in such a small, endangered population, we recommend continuing a disease surveillance program to determine the prognostic factors of survival, understand the role that disease may play during the reintroduction and anticipate disease outbreaks that may pose a risk for the entire reintroduced population. ABSTRACT: The restoration of Iberian lynx (Lynx pardinus) populations in Extremadura (Southwestern Spain) have been carried out since 2014. One of the measures to ensure the success of this program is to examine the effects that diseases may have on reintroduction. Since diseases may be greatly located at certain sites because of the specific ecological requirements of the pathogens and/or vectors, reintroduced individuals may present a risk of infection once released. To determine which pathogens the reintroduced individuals may encounter, we performed a molecular and sero-epidemiological survey in reintroduced and wild-born lynxes. From 2015 to 2019, 69 Iberian lynxes (40 reintroduced and 29 wild-born) were sampled and screened against 10 viral, bacterial and piroplasmid agents. In parallel, 195 sympatric carnivores from the families Canidae, Felidae, Viverridae, Herpestidae and Mustelidae were tested against current or past infections to six common canine/feline viruses. In the Iberian lynx, low contact rates of active infection were obtained for the feline leukemia provirus (FeLV: 1.5%; 1/67), feline parvovirus (FPV: 1.5%; 1/67) and Cytauxzoon sp. (6.7%; 1/15). We also confirmed the emergence of Aujeszky’s disease (suid herpesvirus-1) in this population (SuHV-1: 11.8%; 2/17). Evidence of previous exposure was detected for canine distemper virus (CDV: 5.8%; 3/52), feline coronavirus (1.9%; 1/52), FPV (7.7%; 1/13) and feline calicivirus (FCV: 5.3%; 1/19). From 25 recovered lynx carcasses, we could confirm infectious etiology involvement in the death of four individuals (SuHV-1 in two individuals, coinfection of Cytauxzoon spp. and Aeromonas veronii in one lynx and a Streptococcus canis myositis in another lynx). We confirmed the circulation of CDV, FPV, FeLV, FCV and the feline immunodeficiency virus within the sympatric carnivore community. Due to the low contact rate of infectious agents in such a small, endangered population, we recommend continuing a disease surveillance program to determine the prognostic factors of survival, understand the role that disease may play during the reintroduction and anticipate disease outbreaks that may pose a risk for the entire reintroduced population.